تطبيق كتاب طريقة الحميدية لترقية مهارة الكتابة في مدرسة خط القران دينانيار جومبانج - Suparno, Fathur Rohman; Mu'ad (Al-Wihdah: Jurnal Pendidikan Islam, 2023)
The Hamidiyah method book is one of the learning books to improve writing for the better. Even though this book has not been widely used in other institutions, it is very relevant to be applied in improving writing. One of the institutions that implements this is the Denanyar Al-Qur'an Calligraphy School, Jombang. Uniquely, this book of the Hamidiyah method is mostly only applied in Islamic boarding schools or calligraphy institutions under the auspices of Islamic boarding schools. In addition, this book on the Hamidiyah method has a slightly different application, where the learning is adjusted to the level of understanding of students, not from a specified time. The focus of the problems examined in this thesis are: first, what are the methods of learning Arabic khat using the hamidiyah method in Al-Qur'an calligraphy schools. Second, what are the advantages and disadvantages in learning Arabic that using the hamidiyah method book in Al-Qur'an calligraphy schools.